Pragmatics of Emotions in Intercultural Context - T V Larina (Russian journal of linguistics: Vestnik RUDN, 2015)
The article analyses some ethno-cultural features of emotional/emotive communication which cause failures in intercultural interaction due to misinterpretation of their pragmatic meaning. It demonstrates that pragmatic differences concern the degree of emotional openness and self-control of the speakers, in both verbal and nonverbal communication as well as the sphere of social norms and rules. They are of a systematic character and are predetermined by culture. This thesis is demonstraded with examples from various cultures and a particular emphasis is put on English and Russian language and culture. Focusing on ethnocultural level of communication, I ignore individual peculiarities of communicators and admit to a high level of generalization that is justifiable in intercultural research. The data was taken from theoretical sources, dictionaries, questionnaires and ethnographic observation. I used the methods of pragmatic, contrastive and discourse analyses. The results show that for successful intercultural communication one should possess emotive-cultural competence which is an integral component of intercultural communicative competence.